(untitled) (Global Journal of Human-Social Science, 2011)
The population of beggars on our streets and public spaces is growing exponentially in many urban areas of Tanzania. Today, their presence in the streets of urban areas of developing countries is recognized to be a serious problem that requires urgent redress. This problem is becoming acute and one of the development hindering factors in central zone Tanzania as compared to other zones. This study explores the implications of demographic dimensions on the incidence of street begging in urban areas of central Tanzania with Dodoma and Singida Municipalities as case studies. This study was conducted on different days at different streets and public spaces in Dodoma and Singida Municipalities to obtain data on incidence of street begging. A cross-sectional survey was employed involving 130 street beggars, 60 focus group members and 30 key informants. Structured questionnaires were administered on randomly selected beggars to obtain data on their demographic dimensions. Group discussions, key informant interview, and observations were also used to collect data relevant for the study. The data revealed high incidence of street begging on Friday and during public holidays. The demographic of street beggars reflect that begging is more pronounced among natives or indigenous, physical disabled, male, single, widowed, and Illiterates. Among others, the study recommends that deliberate efforts to improve the socio-economic security of the families of street beggars through empowerment programmes and to embark on public enlightenment on the negative consequences of begging on various dimensions of development.